2017
DOI: 10.1038/nplants.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Shoot-to-root mobile polypeptides involved in systemic regulation of nitrogen acquisition

Abstract: Plants uptake nitrogen (N) from the soil mainly in the form of nitrate. However, nitrate is often distributed heterogeneously in natural soil. Plants, therefore, have a systemic long-distance signalling mechanism by which N starvation on one side of the root leads to a compensatory N uptake on the other N-rich side. This systemic N acquisition response is triggered by a root-to-shoot mobile peptide hormone, C-TERMINALLY ENCODED PEPTIDE (CEP), originating from the N-starved roots, but the molecular nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
304
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(316 citation statements)
references
References 22 publications
10
304
0
2
Order By: Relevance
“…3). Previous studies connecting nutrient acquisition and SSP function in M. truncatula have focused largely on the roles of CLE and CEP genes in N status-dependent root development and nodulation (Mortier et al, 2010;Delay et al, 2013a;Imin et al, 2013;Okamoto et al, 2013;Araya et al, 2014;Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017). Demonstrating the validity of our data sets, we could confirm these previous reports of CLE and CEP regulation (Supplemental Table S7).…”
Section: Hundreds Of Ssps Are Regulated During Nodulation and By Macrsupporting
confidence: 88%
See 2 more Smart Citations
“…3). Previous studies connecting nutrient acquisition and SSP function in M. truncatula have focused largely on the roles of CLE and CEP genes in N status-dependent root development and nodulation (Mortier et al, 2010;Delay et al, 2013a;Imin et al, 2013;Okamoto et al, 2013;Araya et al, 2014;Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017). Demonstrating the validity of our data sets, we could confirm these previous reports of CLE and CEP regulation (Supplemental Table S7).…”
Section: Hundreds Of Ssps Are Regulated During Nodulation and By Macrsupporting
confidence: 88%
“…SSPs encompass many regulatory signaling molecules controlling a multitude of plant growth and development processes, including nodulation and acclimation to nutrient stress (Czyzewicz et al, 2013;Djordjevic et al, 2015;Ohkubo et al, 2017). The identification of such SSPs is of great interest for the improvement of agronomic traits and crop productivity (Bao et al, 2017), particularly in relation to nutrient acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that TGA1/TGA4 should be present in the same cells as ROXY8 and ROXY9. Indeed, Promoter:β‐GLUCORONIDASE ( GUS ) reporter constructs have revealed that both ROXY9 (Ohkubo et al ., ) and TGA1 (Ruiz‐Medrano et al ., ) are expressed in the vascular tissue. Whether expression occurs specifically in the phloem or in the xylem has been determined only for the ROXY9 Prom :GUS construct, this construct has been used to unravel phloem‐specific expression.…”
Section: Discussionmentioning
confidence: 99%
“…The signals that are sent from the shoot to the root are two phloem‐mobile polypeptides called CEP DOWNSTREAM (CEPD1) and CEPD2 that are responsible for CEPR1‐dependent induction of the nitrate transporter NRT2.1 (Ohkubo et al . ). In legumes, CEPs regulate nodulation and lateral root development (Taleski et al .…”
Section: Post‐translationally Modified Peptides and Peptide Familiesmentioning
confidence: 97%